Overcoming barriers to optimizing cash waqf linked sukuk: A DEMATEL-ANP approach - Ryandono, Muhamad Nafik Hadi; Widiastuti, Tika; Filianti, Dian; Robani, Anidah; Al Mustofa, Muhammad Ubaidillah; Dwi Susilowati, Fitriah; Wijayanti, Ida; Dewi, Eka Puspa; Atiya, Nikmatul (Elsevier Ltd, 2025)
The Indonesian government has promoted Cash Waqf Linked Sukuk (CWLS) as an Islamic Social Finance (ISF) initiative. However, as of 2023, only four CWLS series had been issued, with sales falling short of their potential. This study investigates the factors behind low CWLS sales using the Decision Making Trial and Evaluation Laboratory (DEMATEL) and the Analytic Network Process (ANP) methods to analyze the interrelationships between various barriers to CWLS adoption. Primary data was collected from experts in Islamic finance, waqf management, and regulatory institutions through structured interviews and surveys. The DEMATEL method was used to identify cause-and-effect relationships among factors, while ANP ranked the barriers in terms of their significance. The findings reveal that public distrust in CWLS managers (0.052630) is the main issue, followed by concerns about professionalism (0.049331), literacy (0.044858), transparency (0.044482), and competitiveness (0.027556). Based on these findings, the study proposes strategic solutions such as governance standardization, Nazhir certification, and improved public literacy initiatives. These insights offer actionable implications for policymakers, Islamic financial institutions, and waqf stakeholders, providing a practical roadmap to enhance participation, governance, and competitiveness in CWLS and similar Islamic finance instruments. Although technological solutions were not explored, the study provides five strategic recommendations for improving CWLS sales.